2014
DOI: 10.1080/08957959.2014.913042
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity anisotropy in alkali feldspar at high temperature and pressure

Abstract: The electrical conductivity of alkali feldspar along different orientations was determined at 1.0 GPa and at temperatures of 823-1286 K in a cubic anvil apparatus using alternating current impedance spectroscopy. Impedance arcs representing crystal conductivity occur in the frequency range of ∼10 3 -10 6 Hz. The electrical conductivity of alkali feldspar increases with increasing temperature. The highest electrical conductivities in alkali feldspars were measured along the a-axis, with somewhat lower conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Figure 10 shows that the current highly anisotropic conductivity results appear to be consistent with those recently reported for alkali feldspar at atmospheric pressure. [34] The activation enthalpy results obtained here of 1.07 eV-1.23 eV are also very close to the recent values of 0.99 eV-1.02 eV for polycrystalline K-feldspar aggregates reported by Hu et al, [30] 1.05 eV-1.08 eV for single-crystal alkali feldspar reported by Wang et al [33] and 1.04 eV-1.08 eV for single-crystal alkali feldspar reported by El Maanaoui et al, [34] respectively, and also the 0.99 eV migration energy theoretically calculated for K-feldspar by Jones et al [46] Figure 10 also shows some obvious discrepancies between previous studies and the present work, [22,23,26] which appear mainly to be due to differences in measurement method and in the sample chemical composition. Karato and Dai [47] noted that the possibility of discrepancies is due to systematic errors in the calculations of the electrical conductivity of alkali feldspar by using the direct current (DC) and single-frequency alternating current (AC) techniques of some previous studies.…”
Section: Comparison Among Previous Results and Conduction Mechanismsupporting
confidence: 91%
See 2 more Smart Citations
“…Figure 10 shows that the current highly anisotropic conductivity results appear to be consistent with those recently reported for alkali feldspar at atmospheric pressure. [34] The activation enthalpy results obtained here of 1.07 eV-1.23 eV are also very close to the recent values of 0.99 eV-1.02 eV for polycrystalline K-feldspar aggregates reported by Hu et al, [30] 1.05 eV-1.08 eV for single-crystal alkali feldspar reported by Wang et al [33] and 1.04 eV-1.08 eV for single-crystal alkali feldspar reported by El Maanaoui et al, [34] respectively, and also the 0.99 eV migration energy theoretically calculated for K-feldspar by Jones et al [46] Figure 10 also shows some obvious discrepancies between previous studies and the present work, [22,23,26] which appear mainly to be due to differences in measurement method and in the sample chemical composition. Karato and Dai [47] noted that the possibility of discrepancies is due to systematic errors in the calculations of the electrical conductivity of alkali feldspar by using the direct current (DC) and single-frequency alternating current (AC) techniques of some previous studies.…”
Section: Comparison Among Previous Results and Conduction Mechanismsupporting
confidence: 91%
“…[58,59] The 2.51-cm 3 /mole activation volume calculated here suggests that the dominant conduction mechanism of K-feldspar at high temperatures and high pressures involves interstitial potassium ions, which agrees with all of the previous results for tectosilicate minerals. [28][29][30][31][32][33][34] The interstitial ionic potassium is formed according to the point defect reaction as follows: [60]…”
Section: Comparison Among Previous Results and Conduction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…By measuring the resistivity of rocks, important information such as water saturation (Jiang et al, 2021), porosity (Whitman and Yeboah-Forson, 2015), permeability (Kirkby and Heinson, 2017), rock type and composition (Rekapalli et al, 2015;Senger et al, 2021;Bai et al, 2022a) can be determined. Since Archie first proposed the empirical relationship between rock resistivity, porosity, and water saturation (Archie, 1942), scholars have studied the resistivity changes of rocks on this basis and found that the development of fractures (Yin and Xu, 2021), pressure (Wang et al, 2014), saturation (Yang et al, 2022), and frequency (Zhou and Che, 2021) of rocks affect resistivity changes. The frequency of rock fractures significantly affects the variation of resistivity with water saturation which can be used for fracture detection and evaluation (Lee et al, 2021;Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%